Nano-second pulsed laser ablation of inconel 718 and MMPCD for simultaneous optimal ablation rate and surface quality - Ahmed Elkaseer; Islam H. Abdelgaliel; Jon Lambarri; Iban Quintana; Steffen Scholz; Mohamed F. Aly (Scientific Reports)
Abstract This study investigates the ablation performance of Inconel 718, a nickel-based superalloy, and metal matrix polycrystalline diamond (MMPCD), a super composite, using a nano-second (ns) pulsed laser across a range of ablation conditions. Single trenches varying in energy fluence and scanning speeds were created, analyzing the experimental responses in terms of ablation rate and surface roughness. Using regression techniques, models were developed to understand these relationships. Four multi-objective optimization algorithms, weighted value grey wolf optimizer (WVGWO), multi-objective Pareto search (MOPS), multi-objective genetic algorithm (MOGA), and multi-objective sunflower optimization (MOSFO), were employed to optimize these models. Key findings include MMPCD achieving the highest ablation rates at maximum fluence and lower speeds with negligible recast, resulting in smoother surfaces, whereas Inconel 718 reached its peak rates at similar conditions but exhibited significant surface recast. This research provides valuable insights into ns-pulsed laser machining for advanced materials, emphasizing the impact of fluence and scanning speed on achieving high ablation rates and minimal surface roughness.